Codigestão anaeróbia de dejetos de suínos e níveis de inclusão de óleo de descarte - Orrico, Ana C. A. (2015)
Swine manure and lipid residue co-digestion has been widely explored with improvements in substrate degradation, digestion and consequently biogas yield. Thus, we evaluated performance of digesters supplied with swine manure and increasing discarded oil levels, by means of potential of biogas production, and reductions of total solid content (TS), volatile solids (VS) and chemical oxygen demand (COD). To develop co-digestion tests, we prepared substrates composed by swine manure, discarded oil (with 0, 2, 4, 6, 8, 10 and 12% oil in TS substrate), water for dilution of residues and inoculum, having a initial concentration at 4% TS to supply batch-digesters. Maximum TS and VS reductions were 36.8 and 41.1% and occurred at 5.2 and 5.8% oil in substrate. Inclusions of 5.4 and 6.1% oil allowed a potential production range of 222.9 and 263.6 liters of biogas per TS and VS kilogram, which were superior in 10.8 and 5.5 to the observed yields for initial dose of 0% oil. Oil included into substrate with swine manure at doses between 5 and 6% have improved biogas yield.